Adorno and Art - Hellings, J. author. aut Link
XIV, 199 p.
Keywords: A comprehensive, critical and accessible account of Theodor W. Adorno's materialist-dialectical aesthetic theory of art from a contemporary perspective, this volume shows how Adorno's critical theory is awash with images crystallising thoughts to such a degree that it has every reason to be described as aesthetic.